Pemberdayaan Kearifan Lokal Seka Teruna Teruni Sebagai Kader Posyandu Dalam Mengatasi Masalah Kesehatan Remaja - Komang Wiardani, Ni; Dewantari, Ni Made; Heny Achjar, Komang Ayu (Poltekkes Kemenkes Denpasar, 2025)
Background: Various health and nutritional issues for adolescents in Bali require serious attention, such as obesity, malnutrition, and anemia. The efforts to prevent these health problems are needed through the adolescent Posyandu (Integrated Health Care) programObjective: The goal of this activity was to empower Seka Teruma Teruni as Posyandu cadres to address their health issues effectively.Method: The target was Seka Teruna Teruni in Kesiman Kertalangu village, totaling 30 people, taken purposively in 6 banjars. The activity was carried out from June to October 2025. The activity was carried out through education and training in managing adolescent posyandu. The knowledge and skills of cadres were measured using questionnaires and skill checklists.Result: The target group was 30 members of the Teena Teruni Youth Group), 63.3% of whom were female, 50.0% aged 15-18, with the highest education level being high school, and 26.7% were employed. Knowledge was measured before and after training at 79.33 and 91.66, respectively, with an increase of 15.5%. Skills, as measured, also increased by 9.16%.Conclusion: Empowering cadres through education and knowledge can improve their skills and enable them to become Adolescent Integrated Health cadres.